Evaluation of glymphatic system activity by diffusion tensor image analysis along the perivascular space (DTI-ALPS) in dementia patients - Liang, Tian; Chang, Feiyan; Huang, Zhenguo; Peng, Dantao; Zhou, Xiao; Liu, Weifang (British journal of radiology, 2023)
Dementia is a clinical syndrome caused by multiple etiologies, usually manifests with progressive and diffuse brain dysfunction. The activity of the human glymphatic system was evaluated in cases of dementia by the diffusion tensor image analysis along the perivascular space (DTI-ALPS). We recruited 28 healthy subjects and 77 patients, including 38 with Alzheimer's disease (AD),18 with mild cognitive impairment (MCI), 28 with normal controls (NC) and 21 with vascular cognitive impairment (VCI). All participants underwent DTI scanning. Diffusivities in the X, Y and Z axes were obtained in the lateral ventricle body plane of all subjects. We assessed the diffusivity along the perivascular spaces, as well as projection fibers and association fibers, respectively, in order to acquire an DTI-ALPS-index and correlated them with mini mental state examination (MMSE) and montreal cognitive assessment (MOCA) scores using partial correlation which the influence of age was controlled. The AD, MCI, and VCI patients showed significantly lower DTI-ALPS-index ( < 0.001) compared to the NC. Besides, the VCI group had significantly higher DTI-ALPS-index than the AD group ( = 0.007). There was a significant positive correlation between DTI-ALPS-index and MMSE and MOCA scores (the effect of age was controlled), showing that lower water diffusivity along the perivascular spaces associated with dementia.The higher Dzassoc led to the reduced DTI-ALPS-index in VCI, while lower Dxassoc contributed to the decrease of DTI-ALPS-index in AD. The evaluation of DTI-ALPS demonstrates impairment of the glymphatic system in dementia patients by decreased DTI-ALPS-index. Different from AD, the VCI patients show glymphatic drainage disorder rather than glymphatic system impairment. This article comprehensively covers several types of dementia and performs the comparison of VCI, AD and MCI in glymphatic system dysfunction.